Distribution characteristics and risk assessment of heavy metals in seawater, sediment and shellfish in the inner and outer Daya Bay, Guangdong - Yu, Xiaodong; Sun, Lianpeng; Zhu, Xinzhe; Bian, Guojian; Zhou, Wen; Cao, Qian; Hong, Man (Frontiers in Marine Science, 2022)
We investigated the distribution, sources, and ecological risks of heavy metals (As, Hg, Zn, Cd, Pb, Cu, and Cr) in seawater, sediments, and shellfish in the inner and outer waters of Daya Bay. 42 seawater quality survey sites, 21 sediment survey sites and 21 biological survey sites were set up in the study area. Our results showed that Daya Bay’s seawater is both clean and has a high Cu exceedance factor. The sediment heavy metal potential ecological hazard indices are all less than 40, which indicates a minimal degree of risk. ERI in the bay (mean value of ERIis 25.43) and that outside the bay (mean value of 23.56) is lower than 150, so the potential impact on the ecosystem is relatively low. In the Bay, Hg and Zn are primarily from fossil fuel and coal combustion, which enter the ocean via dry and wet deposition or surface runoff. Outside the Bay, Cr, Cu, Zn and Pb are derived the combustion waste gases of ships that enter the ocean via atmospheric deposition. Concerningly, arsenic and lead level in shellfish organisms appear to be above the standard values.However, because THQ and TTHQ are less than 1, there is no potential risk to human health. The weekly assessed intakes (EWIs) of Hg, AS, Pb, and Cd in shellfish inside and outside Daya Bay were 0.093 (0.058 outside the Bay), 0.594 (0.534), 1.115 (1.489), and 0.201 (0.190), respectively, all of these values were lower than the provisional PTWI for humans established by WHO. This indicates that the probability of carcinogenic risk to the population from heavy metals in shellfish are all below unacceptable levels.